Molluscan shellfish safety : proceedings of the 8th ICMSS, Charlottetown, PEI, Canada, June 12-17, 2011 - Sauve', Gilbert (Springer, 2014)
In a time of rapid climatic, industrial and technological changes in molluscan shellfish producing and exporting regions, it is of the utmost importance to keep a keen eye on developing trends. This collection of recent research in molluscan shellfish safety, risk assessment, risk management, regulation and analytical methods presented at the 8th ICMSS (International Conference on Molluscan Shellfish Safety) offers valuable insights in the latest scientific findings